Aktivitas Lalat Rumah (Musca domestica) pada Pemberian Ekstrak Daun Pepaya (Carica papaya) - daesusi, ruspeni; Anindita Riesti Retno Arimurti; Dita Artanti; Fitrotin Azizah; Novaulia Kinasih; Sispita Sari , yeti Eka (Universitas Muhammadiyah Surabaya, 2024)
ABSTRACT House flies (Musca domestica) are vectors or mechanical transmitters of various infectious diseases through their body parts. The use of chemical insecticides to control houseflies has harmful effects on non-target insects, as well as exposure to humans and the environment. The use of insecticides made from natural ingredients is a solution to overcome the use of synthetic chemical insecticides. Papaya (Carica papaya) is a plant that is easy to grow and contains flavonoids, tannins, alkaloids, saponins, papain, calpain, and a number of other secondary metabolic compounds that are anti-mycoorganisms and parasites. This type of experimental research with a post test only group design aims to test the effect of papaya leaf extract on house fly activity. There are 3 treatments, namely P1 (papaya leaf extract), P2 (aquades) and P3 (branded liquid mosquito repellent). Each treatment was repeated 6 times. The research sample was 104 house flies. The results of the Mann Whitney test showed that there was a very significant difference (p<0.01) in the number (presentation) of houseflies that experienced changes in normal activity to abnormal ones between the administration of papaya leaf extract (72%) and the negative control using distilled water (0%). Meanwhile, administering branded liquid mosquito repellent provides 100% of the effect of flies experiencing abnormal activity. Thus, papaya leaf extract has been proven to have potential as a house fly repellent, although the effect is not as great as branded liquid mosquito repellent (p<0.05). Key words: Carica papaya, leaf extract, Musca domestica